4p-3=2p+5

Simple and best practice solution for 4p-3=2p+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p-3=2p+5 equation:


Simplifying
4p + -3 = 2p + 5

Reorder the terms:
-3 + 4p = 2p + 5

Reorder the terms:
-3 + 4p = 5 + 2p

Solving
-3 + 4p = 5 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
-3 + 4p + -2p = 5 + 2p + -2p

Combine like terms: 4p + -2p = 2p
-3 + 2p = 5 + 2p + -2p

Combine like terms: 2p + -2p = 0
-3 + 2p = 5 + 0
-3 + 2p = 5

Add '3' to each side of the equation.
-3 + 3 + 2p = 5 + 3

Combine like terms: -3 + 3 = 0
0 + 2p = 5 + 3
2p = 5 + 3

Combine like terms: 5 + 3 = 8
2p = 8

Divide each side by '2'.
p = 4

Simplifying
p = 4

See similar equations:

| 5(18+x)+10(4x)+25x=1420 | | 75-5n=100 | | 9x-4x+5=x-5+10 | | f(2)=-3x+9 | | 4(2-4r)=72 | | x-5.1=-7.6 | | -3(2x+1)-(x-3)=-2(x-1)+6x-3(2-x) | | 48-8x=36 | | 1/8(8t-6)=t+6/16 | | 22-(x+9)=6x-8 | | 8/5-7/4y=-5/3 | | 88=16-4a | | 3x^2=3-7x | | 5x-6-7x=x+6+x | | 8/9=-1/3w-7/6 | | 9/7-9/2w=-9/5 | | 56+x=10 | | 3w-6=426 | | m^2-4m+3= | | 6+28/4+3*4 | | -3X+7y=-18 | | 6+28/4+3x4 | | 3x-6+13x-6=180 | | 4b+7=25 | | 4x^2+3x=9 | | 4[6-(-5x-6)]=40x+72 | | 3(w+7)=-3(7w-1)+9w | | 7c*6e= | | 8x+10y=48 | | 5a/4-2a/5=17/2 | | 2(x-3)-3=-4(-5x+3)-3x | | 3x+7-5(x-1)=5x+4 |

Equations solver categories